Exploring the Efficiency of Off-Chain vs. On-Chain Transactions in Blockchain Network - Dev Thakkar; Suraj Sabale; Aayushka Waghmare (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Blockchain technology, which offers decentralised, safe, and transparent systems, has completely changed the financial and digital transaction industries. Nevertheless, given the rising use of cryptocurrencies, there are still major issues with transaction speed and scalability. This study explores the workings of blockchain networks’ off-chain and on-chain transaction processes, exploring the reasons for the frequent speed and accessibility advantages of off-chain transactions over on-chain ones. This research paper delves into the mechanisms of off-chain and on-chain transactions within blockchain networks, examining why off-chain transactions are often faster and more accessible compared to their on-chain counterparts. This paper sheds light on the efficiency gap between off-chain and on-chain transactions in cryptocurrency networks, through a comprehensive analysis of the underlying technology, scalability solutions, and practical applications.